Large-Scale Triaxial Testing of TDA Mixed with Fine and Coarse Aggregates - Hany El Naggar; Mohammad Ashari (Buildings, 2023)
The number of scrap tires discarded worldwide is increasing annually. Stockpiling these tires is not a viable option due to environmental concerns and space limitations. Landfilling is likewise unacceptable and is not permitted in many areas. Recycling these tires is the best alternative. Shredding scrap tires to create a product known as tire-derived aggregate (TDA) is one of the most environmentally friendly methods of recycling scrap tires. In the past few decades, TDA and TDA-soil mixtures have been used increasingly in civil engineering projects. Nevertheless, only limited research has so far been conducted on TDA and TDA mixed with soil. In addition, the majority of past research has focused on TDA particles that do not have steel wires and are small in size. In the present research, triaxial tests were performed on various mixtures of TDA with sand or gravel. Each sample was subjected to three different confining pressures. The results of the tests are presented and discussed, and empirical equations are proposed to match the laboratory results.